Advanced Materials for Clothing and Textile Engineering - Rogale, Dubravko; Rogale, Snježana Firšt (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the research of textile materials for conventional and protective clothing. More than ever, multidisciplinary research applied to the field of new textile materials and new techniques of processing and joining materials is needed. The main research topics of this Special Issue include research and development of new materials and the improvement of their properties, and the mechanical and thermal properties of yarns, materials and clothing. Simulations based on the physical and mechanical properties of fabrics for the purpose of prediction assessment of the appearance and behavior of clothing, as well as 3D virtual garment prototypes using 3D body models and involving 3D human-body scanning, are interesting and significant topics in the field of clothing engineering. The problem of microplastics that are produced during the manufacture or cleaning of synthetic textiles has also been investigated in this Special Issue.